The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.2967/jnumed.107.044339
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Pre- to Postsynaptic Mismatch of the Cardiac Sympathetic Nervous System in Ischemic Congestive Heart Failure

Abstract: Pre-and postsynaptic cardiac sympathetic function is altered in ischemic congestive heart failure (CHF). Whether there is a presynaptic-to-postsynaptic mismatch or whether mismatch is related to adverse cardiac events is unknown. Methods: In 13 patients with ischemic CHF and 25 aged-matched healthy volunteers, presynaptic function was measured by PET of 11 Cmeta-hydroxyephedrine ( 11 C-mHED), a norepinephrine (NE) analog. Postsynaptic function, b-adrenergic receptor (BAR) density (B9 max ), was measured by ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
46
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(46 citation statements)
references
References 29 publications
(46 reference statements)
0
46
0
Order By: Relevance
“…Table 2 provides an overview. Combinations of autonomic imaging agents have, for example, been used to identify an imbalance between presynaptic neuronal integrity and postsynaptic receptor density in progressive heart failure (18), to show that postsynaptic receptor density and downstream signaling may be impaired despite intact presynaptic catecholamine uptake in adriamycin-induced cardiotoxicity (19) or to show that parasympathetic muscarinic receptors may be upregulated after myocardial infarction (20).…”
Section: Beyond Nerve Terminal Functionmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 2 provides an overview. Combinations of autonomic imaging agents have, for example, been used to identify an imbalance between presynaptic neuronal integrity and postsynaptic receptor density in progressive heart failure (18), to show that postsynaptic receptor density and downstream signaling may be impaired despite intact presynaptic catecholamine uptake in adriamycin-induced cardiotoxicity (19) or to show that parasympathetic muscarinic receptors may be upregulated after myocardial infarction (20).…”
Section: Beyond Nerve Terminal Functionmentioning
confidence: 99%
“…This ability helps to clarify the importance of regional heterogeneity versus globally impaired innervation. Of note, new 18 F-labeled tracers, such as 18 F-LMI1195, are under investigation and may become a commercial product in the future (12).…”
Section: Cardiac Neuronal Petmentioning
confidence: 99%
See 1 more Smart Citation
“…Research with compounds labeled with tritium ( 3 H), 14 C, and 125 I laid the groundwork for the development of compounds labeled with g-and positron-emitting radioisotopes (6). These latter developments permitted external imaging of living animals with scintillationdetection devices and gave rise to the use of nuclear medicine techniques for neuronal imaging in the second half of the 20th century (7)(8)(9)(10).…”
mentioning
confidence: 99%
“…An impaired function of presynaptic sympathetic nerve terminals is considered to reflect impaired reuptake and thus impaired removal of the neurotransmitter from the synaptic cleft [1], resulting in overexposure of the myocardium to catecholamines and in a pre/post-synaptic signaling imbalance [2]. Consistent with this pathophysiologic model, prospective, large-scale clinical trials confirmed an excellent prognostic value of adrenergic imaging in patients with heart failure, both with single photon emission tomography (SPECT) and with positron emission tomography (PET) [3,4].…”
mentioning
confidence: 99%